2010
DOI: 10.1038/leu.2010.184
|View full text |Cite
|
Sign up to set email alerts
|

High frequencies of leukemia stem cells in poor-outcome childhood precursor-B acute lymphoblastic leukemias

Abstract: In order to develop a xenograft model to determine the efficacy of new therapies against primary human precursor-B acute lymphoblastic leukemia (ALL) stem cells (LSCs), we used the highly immunodeficient non-obese diabetic (NOD).Cg-PrkdcscidIL2rgtmlWjl/SzJ (NOD-severe combined immune deficient (scid) IL2rg−/−) mouse strain. Intravenous transplantation of 2 of 2 ALL cell lines and 9 of 14 primary ALL cases generated leukemia-like proliferations in recipient mice by 1–7 months after transplant. Leukemias were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 57 publications
(109 reference statements)
5
46
0
Order By: Relevance
“…However, immunophenotypic analysis showed that engrafted B-ALL cells, compared with the original sample, maintained CD45 and CD10, but not CD19 expression. The mechanism underlying the absence of CD19 surface expression in engrafted human cells may be ascribed to posttranscriptional events, as described 26 and/or related to their acquisition of a more immature phenotype possibly induced by microenvironmental conditions. In addition, it was suggested that ETV6-RUNX1-positive cells capable of reconstituting leukemia upon transplantation to NOD-SCID mice have the CD19 À phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, immunophenotypic analysis showed that engrafted B-ALL cells, compared with the original sample, maintained CD45 and CD10, but not CD19 expression. The mechanism underlying the absence of CD19 surface expression in engrafted human cells may be ascribed to posttranscriptional events, as described 26 and/or related to their acquisition of a more immature phenotype possibly induced by microenvironmental conditions. In addition, it was suggested that ETV6-RUNX1-positive cells capable of reconstituting leukemia upon transplantation to NOD-SCID mice have the CD19 À phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Thus, six early pre (CD19 þ CD10 þ ) B-ALL cell suspensions (Pt 3, 9, 15, 16, 17 and 18) were injected i.v. in two groups of five animals each (controls and IL-27-treated mice) and killed 6-8 weeks later when signs of poor health became evident in controls.…”
Section: Il-27 Inhibited B-all Cell Spreading In Nsg Micementioning
confidence: 99%
“…Currently, much debate surrounds LSCs in childhood ALL with evidence identifying candidate LSCs in both rare, immature populations as well as conversely, across several immunophenotypically distinct groups. 9,10,[18][19][20][21] It is unlikely that we can clinically exploit current evidence to effectively re-direct flow cytometric MRD monitoring towards the LSC compartment until the immunophenotype of the cells which maintain the leukemia are more clearly defined. …”
mentioning
confidence: 99%
“…In precursor T-acute lymphoblastic leukaemia (ALL), the frequency of LSCs (defined as cells that initiate leukaemic engraftment in a xenograft recipient) is reported to range from one in 10 5 -10 7 following intravenous injection into non-obese diabetic severe combined immunodeficient (NOD/SCID; NS) mice (Cox et al, 2007;Chiu et al, 2010), or one in 10 3 -10 5 where the more immunodeficient NOD.Cg-Prkdc scid Il2rg tm1Wjl /SzJ (NSG) strain is used (Armstrong et al, 2009;Chiu et al, 2010). In precursor B-ALL, NS xenograft-initiating cell frequencies of one in 10 5 -10 7 have been reported (Cobaleda et al, 2000), with higher frequencies observed following intrafemoral transplant into NSG mice (one in 40-10 3 ; le Viseur et al, 2008;Rehe et al, 2013) or where cells from chemorefractory patients are used (one in 10-10 2 ; Morisot et al, 2010). The cellular organization of ALL has variably been argued to be hierarchical (Cobaleda et al, 2000;Cox et al, 2007;Hong et al, 2008) or non-hierarchical (le Viseur et al, 2008Diamanti et al, 2012;Rehe et al, 2013), the latter being based on the identification of LSCs in all of the variable immunophenotypic sub-populations of the disease.…”
Section: Very High Frequencies Of Leukaemia-initiating Cells In Precumentioning
confidence: 99%